CRITICAL DISCOURSE ANALYSIS OF SOCIO-CULTURAL CONTENT AND POST-PANDEMIC THEMES IN ENGLISH TEXTBOOKS FOR JUNIOR HIGH SCHOOL - Chandra, Tan Michael; Yuliani, Fitria (Premise: Journal of English Education and Applied Linguistics, 2024)
The post-pandemic landscape, shaped by COVID-19, has ushered in substantial socio-cultural shifts, particularly in teaching and learning practices. The transition from traditional in-person learning to rapid adoption of online methods, followed by a return to in-person learning, necessitated adjustments in educational habits. This transformation is further emphasized by the Merdeka curriculum's implementation in the Academic Year 2022/2023, influencing the approach of textbook authors. This research uses Critical Discourse Analysis (CDA) and Fairclough's three-dimensional model to scrutinize five 7th-grade English textbooks from different publishers within the Merdeka curriculum framework. The analysis explores the socio-cultural and post-pandemic content, providing nuanced insights into how these materials address challenges and transformations induced by the COVID-19 pandemic. Acknowledging the inherent connection between language and socio-cultural elements, the study examines how the textbooks balance Western influences with Indonesian socio-cultural content. Additionally, it investigates how the textbooks incorporate memories of the global pandemic, contributing to the evolving landscape of English education in Indonesia.